Unplanned migration flow: the acceptance system response, Perugia: Running title: Migrant flow in Perugia - Gianfredi, Vincenza; Moretti, Massimo; Gigli, Massimo; Fusco-Moffa, Igino (Acta Biomedica Atenei Parmensis, 2019)
Background and aim of the work: Since several years, Italy is facing an important flow of immigration. Umbria is not a region of disembarkation of refugees, nevertheless is one of the Italian regions with the highest rate of foreign population compared to the total resident population. Aim of this paper is to collect data on migrants and refugees’ health care services access, focusing on migrants’ characteristics arrived and living in Umbria. Methods: We conducted a retrospective cohort study at the Local Health Unit Umbria of Perugia, Italy. Descriptive analysis was performed in order to identify the characteristics of the migrants living in Perugia area. Data analysis was performed using Excel® software. All frequencies are expressed as percentage. Results: Between 2015-2017, 2,688 migrants came to Umbria Region. The mean age is 23.6 years, almost all are male, and however the majority of female comes from Nigeria. Only 25.5% of migrants durably sojourned in Umbria Region, and only half of them are residents and received the assignment of general practitioner. Conclusions: Unplanned migration may cause an abrupt rupture of the social-cultural supports that sustain both psychological and physical well-being. Regional Health Service should collect data on migrants and refugees’ health and their health care services access, in order to offer an efficient and appropriate regional health system.